Trends in fatal and nonfatal overdose by race among people who inject drugs in Baltimore, Maryland from 1998 to 2019. (1st December 2021) - Genberg, Becky L.; Gicquelais, Rachel E.; Astemborski, Jacquie; Knight, Jennifer; Buresh, Megan; Sun, Jing; German, Danielle; Thomas, David L.; Kirk, Gregory D.; Mehta, Shruti H.
Abstract: Objective: The objective of this study was to examine trends in fatal and nonfatal overdose in a community-based sample of current and former people who inject drugs (PWID). Methods: Data from 4826 current and former PWID from the AIDS Linked to the IntraVenous Experience (ALIVE) observational cohort study in Baltimore, Maryland, were used to characterize fatal and nonfatal overdose rates from 1998 to 2019. Poisson regression was used to examine factors associated with nonfatal overdose and differences by race among 1052 PWID between 2014 and 2019. Results: Fatal overdose rates reached a high of 13 per 1000 person-years in 2018. Among 1052 current and former PWID, of whom 75% were Black and one-third were female, the nonfatal overdose rate of 529 per 1000 person-years in 2019 was 8 times higher than 2014 (incidence rate ratio [IRR]=7.76, 95% CI: 3.35, 18.0). The annual adjusted increase in nonfatal overdose rate was 53% among Black PWID (IRR=1.53, 95% CI: 1.34, 1.75), compared to 14% among White PWID (IRR=1.14, 95% CI: 0.88, 1.46). Urban residence, opioid use, depressive symptoms, and hepatitis C infection were positively associated with nonfatal overdose among Black PWID. Recent injection drug use and tranquilizer use was associated with increased overdose among Black and White PWID. Conclusions: Rates of fatal and nonfatal overdose were high and increased from 2014 to 2019 among current and former PWID, with the most dramatic increases in nonfatal overdose observed among Black PWID. These findings highlight the urgent need for additional resources to reduce the differential harms associated with opioids by race. Highlights: Fatal overdose rates in this PWID sample peaked at 13 per 1000 person-years in 2018. Non-fatal overdose rates were 8 times higher in 2019 compared to 2014. The most dramatic increase in non-fatal overdose rates were among Black PWID. Interventions to reduce the differential harms of overdose by race are needed.